Stimulating ODL research at UNISA: exploring the role and potential impact of the UNESCO Chair. (4th May 2021) - Letseka, Moeketsi
ABSTRACT: This paper offers insights into the establishment of the United Nations Educational, Scientific and Cultural Organisation (UNESCO) Chair of Open Distance Learning (ODL) at the University of South Africa (UNISA). The aim of the UNESCO Chair is to stimulate ODL research at UNISA. The paper briefly describes UNISA, which is the largest dedicated distance education institution on the continent of Africa, with student enrolments in excess of 300, 000. Notwithstanding its size and mandate to provide expanded access to quality higher education to previously excluded blacks, UNISA is hampered by a lack of capacity in ODL research in the form of articles, the UNESCO Chair at UNISA was established to respond to this challenge of a lack of ODL research capacity. The paper (1) provides a brief outline of the UNITWIN/UNESCO Chairs Programme; (2) outlines the objectives of the Chair in relation to UNISA's challenges of capacity for technology-assisted teaching, learning and research; (3) maps out the imperative for technology-supported teaching, learning and research at UNISA with respect to digital literacy, digital proficiency, and digital fluency ; and (4) closes with some concluding remarks.